The 'Abbasid and Carolingian Empires : comparative studies in civilizational formation - Tor, D. G. (Islamic History and Civilization, 2017)
Circa AD 750, both the Islamic world and western Europe underwent political revolutions; these raised to power, respectively, the ʿAbbasid and Carolingian dynasties. The eras thus inaugurated were similar not only in their chronology, but also in the foundational role each played in its respective civilization, forming and shaping enduring religious, cultural, and societal institutions. The ʿAbbāsid and Carolingian Empires: Studies in Civilizational Formation , is the first collected volume ever dedicated specifically to comparative Carolingian-ʿAbbasid history. In it, editor D.G. Tor brings together essays from some of the leading historians in order to elucidate some of the parallel developments in each of these civilizations, many of which persisted not only throughout the Middle Ages, but to the present day. Contributors are: Michael Cook, Jennifer R. Davis, Robert Gleave, Eric J. Goldberg, Minoru Inaba, Jürgen Paul, Walter Pohl, D.G. Tor and Ian Wood.